ChemInform Abstract: Donor—Acceptor Cyclopropanes as 1, 2‐Dipoles in GaCl3‐Mediated [4 + 2]‐Annulation with Alkenes: Easy Access to the Tetralin Skeleton. Issue 3 (29th December 2015) - Novikov, Roman A.; Tarasova, Anna V.; Korolev, Victor A.; Shulishov, Evgeny V.; Timofeev, Vladimir P.; Tomilov, Yury V.
Abstract: In this new process donor‐acceptor cyclopropanes act as sources of formal 1, 2‐ and 1, 4‐dipoles to afford polysubstituted tetralins in a regio‐ and diastereoselective manner.